Pengaruh Literasi Keuangan Dan Tingkat Suku Bunga Terhadap Keputusan Pengambilan Kredit di PT Pegadaian UPC Walian - Kawengian, Lira Lusiana; Kantohe, Meidy S. S.; Tuegeh, Octavia (Journal of Culture Accounting and Auditing, 2025)
This research aims to analyze the influence of financial literacy and interest rates on credit decision-making at PT Pegadaian UPC Walian. This study employs a quantitative research approach using primary data collected through questionnaires distributed to 100 customers selected using incidental sampling techniques. Data analysis was conducted using multiple linear regression with SPSS version 27. The findings indicate that financial literacy and interest rates simultaneously have a significant effect on credit decision-making. Partially, financial literacy has a positive and significant effect on credit decisions, meaning that the higher the customers’ level of financial literacy, the more accurate their decisions in taking credit. Moreover, interest rates also significantly influence credit decision-making, showing that lower interest rates increase customers’ interest and decisions to obtain credit. Thus, both variables play an essential role in influencing customers’ credit decision-making at PT Pegadaian UPC Walian.